Learning Motivation From The Perspective Of Educational Psychology: an Analysis Based On Study Habits and Learning Environment - Mohammad Syamsul Maarif; M. Yunus Abu Bakar (International Journal of Interdisciplinary Research, 2025)
This study aims to analyze learning motivation from the perspective of educational psychology, with a particular emphasis on the role of study habits and the learning environment. Employing a descriptive qualitative approach through library research, the study reviews a range of scholarly literature, including academic books, journal articles, and relevant research findings. The analysis reveals that learning motivation is shaped by both internal factors (such as study habits, self-efficacy, and self-regulation) and external factors (including the physical and psychological aspects of the learning environment). The Self-Determination Theory (SDT) serves as the primary theoretical framework, highlighting the importance of fulfilling three basic psychological needs: autonomy, competence, and relatedness. Effective study habits such as structured planning, self-testing, and time management are found to significantly enhance student engagement and academic performance. Likewise, a supportive learning environment that fosters student autonomy and promotes positive teacher-student relationships contributes to the development of intrinsic motivation. The dynamic interaction between study habits and the learning environment creates a motivational and sustainable educational ecosystem. In conclusion, student learning motivation can be substantially enhanced by cultivating positive study habits and establishing a supportive learning environment, thereby informing the development of more adaptive educational policies and practices.